2021
DOI: 10.3390/antiox10081237
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Does Not Influence Subjective Pain Sensation in Inflammatory Bowel Disease Patients

Abstract: Oxidative stress (OS) has been proposed as a significant causative and propagating factor in inflammatory bowel diseases (IBDs). Modulation of OS is possible through antioxidants and inhibition of oxidizing enzymes. Thirty-one IBD patients and thirty-two controls were included in the study. The aim was to examine the levels of OS in colonic tissue of IBD requiring surgical intervention and control group, and their association with pain intensity. Total antioxidant capacity (TAC), superoxide dismutase (SOD) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…In the present study, we noticed depletion of colon GSH, GPx, CAT, and SOD in DSS-treated rats. Our results were in line with the results reported by Zieliska et al 66 , who observed a significant decrease in GSH, GPx, CAT, and SOD levels in patients with IBD when compared with controls. Our results indicate that the administration of CAPE significantly improves macroscopic damage, colon length, increases the activity of GPx, CAT, and SOD, depresses TBARs and NO levels, and increases GSH levels in the colon tissues of experimental colitis.…”
Section: Effect Of Cape and Sulfasalazine On Colon Gsh Gpx Cat And So...supporting
confidence: 94%
“…In the present study, we noticed depletion of colon GSH, GPx, CAT, and SOD in DSS-treated rats. Our results were in line with the results reported by Zieliska et al 66 , who observed a significant decrease in GSH, GPx, CAT, and SOD levels in patients with IBD when compared with controls. Our results indicate that the administration of CAPE significantly improves macroscopic damage, colon length, increases the activity of GPx, CAT, and SOD, depresses TBARs and NO levels, and increases GSH levels in the colon tissues of experimental colitis.…”
Section: Effect Of Cape and Sulfasalazine On Colon Gsh Gpx Cat And So...supporting
confidence: 94%
“…( 20 ) In IBD patients, a significant decrease of SOD activity and GSH level was seen. ( 21 ) Sirt3 has been demonstrated to regulate oxidative stress by modulating key antioxidants. Mechanistically, Sirt3 directly deacetylates the MnSOD 122-lysine residue in the mitochondria, enhancing its ability to neutralize ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Formononetin, as an active component of flavonoids extracted naturally, was recently applied in a variety of disease models as a new inflammatory inhibitor and may have potential therapeutic value for IBD by activating Nrf2 expression[ 21 ]. Zielińska et al [ 22 ] showed that stigmasterol significantly reduced the inflammatory factors IL-1β, IL-6, and MCP-1 and the related cytokine synthase COX-2, inhibited colon shortening, and reduced the severity of IBD. These researchers also found that stigmasterol had greater anti-inflammatory activity than β-sitosterol and inhibited the symptoms of colitis[ 23 ].…”
Section: Discussionmentioning
confidence: 99%